Atomic metal, N, S co-doped 3D porous nano-carbons: Highly efficient catalysts for HT-PEMFC. (6th April 2021) - Liu, Wenqi; Chen, Qingjun; Zhang, Feng; Xu, Dongyan; Li, Xiaojin
Abstract: A new strategy for fabricating atomically dispersed heteroatom-doped nanoporous carbon materials is reported. Through the self-assembly of dopamine, triblock copolymer F127, and metal ions, different three-dimensional atomic metal-N/S doped carbon catalysts are obtained after pyrolysis. Noble metal salts with ferrous sulfate induce the bimetallic monatomic FeM (M = Pd, Pt) N, S-doped carbon catalysts. Minute amounts of Pt or Pd single atoms in the catalysts greatly improve the oxygen reduction reaction (ORR) activity both in acidic and alkaline conditions. Typically, the obtained Fe, Pt–N/S co-doped carbon (FePt-NSC) catalyst exhibits superior ORR performance with positive half-wave potentials (E1/2 ) of 0.89 and 0.80 V in alkaline and acidic solutions, respectively. In addition, FePt-NSC displays dominant four electron catalytic process and excellent electrocatalytic stability. The high temperature proton exchange membrane fuel cell (HT-PEMFC) test (160 °C) illustrates that FePt-NSC reaches 0.67 V at 400 mA/cm 2 and achieves the peak power density of 628 mW/cm 2, better than most of the catalysts reported at the similar conditions. These results indicate the atomic metal-N/S doped porous carbon catalysts to be highly promising low-Pt catalysts for HT-PEMFC. Highlights: Nano-porous structured low-cost catalysts were synthesized. Atomic metal atoms and N/S-doping synergistically enhanced the ORR activity. The catalysts exhibit high catalytic performance in alkaline and acidic medium. The catalysts show similar performance to commercial Pt/C in HT-PEMFC.